Implantación del sistema de contabilidad comercial, por el sistema de cuenta permanente y aplicación de la NIC 2 en “calzado palacios” de la ciudad de Cariamanga, cantón calvas, provincia de Loja, durante el periodo mayo- junio del 2016 - Troya Jiménez, Karla Alexandra (2016)
This thesis entitled: IMPLEMENTATION OF THE COMMERCIAL ACCOUNTING SYSTEM, BY THE SYSTEM OF PERMANENT ACCOUNT AND APPLICATION OF IAS 2 IN “FOOTWEAR PALACIOS" CITY CARIAMANGA, CALVAS CANTON, LOJA PROVINCE, DURING THE PERIOD MAY-JUNE 2016 ,was developed in order to comply with the Academic Regime Regulation of the National University of Loja, as one of the requirements previous to obtain the degree of Engineer in Accounting and Auditing, Counter Public Auditor CPA, as well as to provide the owner with an accounting tool that allows you to provide reliable and timely information. By developing research were complied with the objectives, in relation to, the design of the plan and the manual of accounts, the accounting process through the control system of permanent inventory, IAS 2 was applied to control inventory, which allowed provide information more real on the economic movement of the business. They were designed internal documents, accounting records as the daily book, ledger and trial balance; between the auxiliary records highlights the record of inventories, kárdex cards, reports of purchase and sale, the same that facilitated the application of the accounting process and the presentation of the financial statements. Finally it is determined that the application of an accounting system is of vital importance for the control transactional movement of FOOTWEAR PALACIOS, since it will allow you to know the results and contribute to the decision-making to achieve its development.